Literary achievements of Iranian literary research organization Miras-e-Maktoob (From 1992 to 2022) - Dr. samiullah; Dr. Majid Mushtaq (Zaban-o-Adab, 2023)
In the field of literature and literary research Iranian research organisation named MIRAS-E-MAKTOOB is a well-known organisation with a reputation for research in Persian language and literature, Islamic literature, Iranian literature, Islamic Iranian Literature, culture and civilization. Classical and modern literature in any form related to these topics is the special focus of this research organisation. Compilation of lists of manuscripts of different countries, Collections of literary works, bibliographies, editing and translations of manuscripts and other important books are major achievements of his research organisation. It has also arranged many literary national and international conferences and workshops. In this article a brief summary of its literary works is being presented.